Increasing young children's honest reports and decreasing their transgressions. Issue 1 (17th November 2022) - Lehardy, Robert K.; Luczynski, Kevin C.; Stocco, Corey S.; Fallon, Maya J.; Rodriguez, Nicole M.
Abstract : Young children break rules (i.e., transgress) and then lie about those transgressions. By adolescence, lying is associated with decreased trust, communication, and quality of relationships, and with befriending antisocial peers. To decrease lies, we replicated differentially reinforcing honest reports about transgressions for one 6‐year‐old neurotypical child and two 7‐year‐old children who were diagnosed with autism spectrum disorder. After all children learned to report honestly about transgressions, we extended past research to decrease transgressions by differentially reinforcing alternative play behaviors. For all children, this resulted in increased levels of play, decreased transgressions, and continued honesty about infrequent transgressions. Caregivers were satisfied with children's increased honest reports and decreased transgressions. The results support first reinforcing children's honest reports about transgressions and then decreasing transgressions to satisfying levels for caregivers.